2009
DOI: 10.1111/j.1440-172x.2009.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations of health‐care professionals sharing and contributing responsibility in paediatric caring situations

Abstract: This study aimed to identify, describe and generate concepts regarding health care professionals' information exchanges with minors and/or their parents/guardians in paediatric caring situations. The study took place at three paediatric outpatient units at a university hospital and there were 15 health care professionals involved. Using the grounded theory and the constant comparative analysis methods, the data collection and analysis was undertaken simultaneously, using participant observation, review of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In a recent multinational study, receiving information at diagnosis, and having access to multiple sources of information later, have been associated to better outcomes from young patients' and parents' perspectives [36]. The most frequently used source were diabetes medical teams, which might have valuable information to add in online dialogues provided they communicate in "the right way"-whatever that means [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent multinational study, receiving information at diagnosis, and having access to multiple sources of information later, have been associated to better outcomes from young patients' and parents' perspectives [36]. The most frequently used source were diabetes medical teams, which might have valuable information to add in online dialogues provided they communicate in "the right way"-whatever that means [37].…”
Section: Discussionmentioning
confidence: 99%
“…These authors assert that negotiation depends on the development of relationships between the family and health care providers (Corlett & Twycross, 2006b). In fact, power struggles are still associated with parental participation in their children's care (Coyne, 2008a;Coyne & Cowley, 2007;Lee, 2007;Martenson et al, 2009;McPherson et al, 2011;Priddis & Shields, 2011) and a gap exists between nurses' expectations and parents' attitudes (O'Haire & Blackford, 2005;Young et al, 2006).…”
Section: Models Of Partnershipmentioning
confidence: 95%
“…Parents are now seen as consumers of care and are therefore entitled to honest and complete information from caregivers, the right to frequent interactions with staff, and participation in their children's care (Martenson et al, 2009;McQueen, 2000;Priddis & Shields, 2011;Sobo, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this SCA (Haase et al, 2000) revealed how the ethical demand (Lögstrup, 1997) in the information exchange in pediatrics is conceptualized and visualized in a five-concept process model (Figure 1). An additional strength is that the concept process model is grounded in empirical data from three observational grounded theory (GT) studies Mårtenson et al, 2008a;Mårtenson et al, 2008b). This use of empirical GT data is here seen as modifiability (Glaser, 1978) of these studies, modifiability is openness to development when the findings can be used in new research and be modified by new results.…”
Section: Discussionmentioning
confidence: 99%
“…Two other grounded theory studies focused on the process of information exchange between parents and guardians of medically ill children (Mårtenson, Berterö, & Fägerskiöld, 2008a) and the children's nurses (Mårtenson, Fägerskiöld, & Berterö, 2008b). In these studies the parents resolved their main concerns in the information exchange by firm handling of the situation, while the professional staff did it by sharing and contributing to their perceived responsibilities.…”
Section: Relevant Literaturementioning
confidence: 99%